2003
DOI: 10.1093/hmg/ddh038
|View full text |Cite
|
Sign up to set email alerts
|

Genomic imprinting at the WT1 gene involves a novel coding transcript (AWT1) that shows deregulation in Wilms' tumours

Abstract: The Wilms' tumour suppressor gene, WT1, is mutated in 10-15% of Wilms' tumours and encodes zinc-finger proteins with diverse cellular functions critical for nephrogenesis, genitourinary development, haematopoiesis and sex determination. Here we report that a novel alternative WT1 transcript, AWT1, is co-expressed with WT1 in renal and haematopoietic cells. AWT1 maintains WT1 exonic structure between exons 2 and 10, but deploys a new 5'-exon located in intron 1 of WT1. The AWT1 gene predicts proteins of approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
68
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 24 publications
5
68
1
Order By: Relevance
“…We have previously shown that the WT1 locus at 11p13 expresses two imprinted transcripts: the noncoding antisense RNA WT1-AS (21) and the alternate coding transcript AWT1 (22). Hypomethylation of the DMR in the WT1 ARR is associated with LOI of the WT1-AS and AWT1 transcripts (21,22,25).…”
Section: Loi At 11p13mentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that the WT1 locus at 11p13 expresses two imprinted transcripts: the noncoding antisense RNA WT1-AS (21) and the alternate coding transcript AWT1 (22). Hypomethylation of the DMR in the WT1 ARR is associated with LOI of the WT1-AS and AWT1 transcripts (21,22,25).…”
Section: Loi At 11p13mentioning
confidence: 99%
“…These imprinted transcripts are the noncoding antisense RNA WT1-AS (21) and the alternate coding transcript AWT1, which gives rise to NH 2 -terminally truncated WT1 proteins (22). We have shown that in a subset of WTs, LOI of these imprinted WT1 transcripts occurs, leading to their biallelic expression (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…3,[10][11][12] At least 36 isoforms of WT1 protein are produced from the same DNA template as a result of alternative transcription initiation, alternative pre-mRNA splicing, mRNA editing and alternative translation initiation. 1,3,5,10,[13][14][15][16][17][18] The four major WT1 isoforms are generated by an alternative splicing and vary in the presence or absence of so called 17AA insert (17 amino acids encoded by the whole exon 5) and KTS insert (according to the three amino acids leucinethreonine-serine encoded by the terminal sequence of exon 9)- [19][20][21][22][23] An alternative WT1 transcript, AWT1 (also short transcript, sWT1), maintains WT1 exonic structure between exons 2 and 10 but uses another first exon located in intron 1 of WT1 (exon 1a). It may otherwise exist in all splicing variants characteristic of WT1.…”
Section: Introductionmentioning
confidence: 99%
“…It may otherwise exist in all splicing variants characteristic of WT1. 14,15 Another N-terminally truncated transcript, lacking exons 1-5, has been previously described and the presence of a cryptic promoter within WT1 intron 5 hypothesized. 24,25 All of these modifications markedly influence the activity of WT1 protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation